(untitled) (Al-Academy, 2024)
Explanation of article events , or discribing it establish to anderstanding an phenomenon which its effects still clear in the art , surching like this may be very usful in the analysis of new art , which considering one of the most important turns in the history of art . and if we look to human body in the art as existenc in the art , from it’s begening to the modern age . so we can understand the meaning of this existence and it’s directins which cover all the worid and the lead us to thiories and suggestion’s help in understand to this direction and the effects between our arts and the external directions.